Funcionabilidad familiar en la violencia escolar de los estudiantes de 9° de una Institución Educativa de Hatonuevo- La Guajira - Ortiz, Yolanda María; López Andrade, Karen Milena (Universidad Antonio Nariño, 2024)
The general objective of the following research is to analyze the incidence of family functionality in school violence among 9th grade students of an Educational Institution in Hatonuevo-La Guajira. To do this, we worked with a quantitative and correlational methodology in which 2 instruments were applied, the first was the Aggression Questionnaire (Buss and Perry) and the other was the Family Apgar, this application was carried out on 77 minors of grade ninth of the institution. The results regarding family functioning show that there is a high percentage of students with family dysfunction, 38% of the participants perceive severe dysfunction, followed by 37% with moderate dysfunction and only 25% with normal functionality.